2019
DOI: 10.1111/asj.13162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different levels of dietary protein with or without plant extract YGF251 on growth performance, nutrient digestibility, blood profiles, fecal microbial shedding, and fecal gas emission in growing pigs

Abstract: This experiment was conducted to evaluate the effects of plant extract YGF251 supplementation in different protein level diets on growth performance, nutrient digestibility, blood profiles, fecal microbial shedding, and fecal gas emission in growing pigs. A total of 144 pigs (24.72 ± 1.54 kg) were randomly assigned to the treatments in a 2 × 3 factorial arrangement of dietary protein levels (15.50%, 14.00% or 12.50%) and plant extract YGF251 levels (0 or 0.05%) with 6 replications per treatment and 4 pigs per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Devi et al (2015) observed that, in growing pigs fed a diet supplemented with YGF251 (0.05 or 0.10%), ADG increased while ADFI and FCR were not affected. However, Lei et al (2019) noted that ADG, ADFI, and FCR were not improved in growing pigs fed a diet supplemented with 0.05% YGF251. Devi et al (2015) suggested that the improvement in ADG of pigs fed a diet supplemented with YGF251 (0.05 or 0.10%) was due to the amelioration of plasma IGF-1 concentration.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Devi et al (2015) observed that, in growing pigs fed a diet supplemented with YGF251 (0.05 or 0.10%), ADG increased while ADFI and FCR were not affected. However, Lei et al (2019) noted that ADG, ADFI, and FCR were not improved in growing pigs fed a diet supplemented with 0.05% YGF251. Devi et al (2015) suggested that the improvement in ADG of pigs fed a diet supplemented with YGF251 (0.05 or 0.10%) was due to the amelioration of plasma IGF-1 concentration.…”
Section: Discussionmentioning
confidence: 96%
“…As reported by Yin et al (2018), due to the fecal microbial was ameliorated in pigs fed a diet supplemented with herbal extract, thus, the nutrient digestibility and the fecal gas emission were improved. Lei et al (2019) noted adult pigs were fed a diet supplemented with YGF251. A dose below 0.05% did not affect the intestinal microbial balance, and thus did not impact nutrient digestibility.…”
Section: Discussionmentioning
confidence: 99%
“…Natural bioactive compounds can prevent the animal growth check and enhance gastrointestinal health. Phytogenic feed additives have been widely used in view of the plant-derived properties and growth-promoting effect, which suggests that phytogenic feed additives will be a promising alternative to antibiotic growth promoters ( 21 , 31 ). It is shown that the 300 ppm Laminarin group has a higher ADFI (average daily feed intake) and a higher ADG (average daily gain) than the basal group ( 32 ).…”
Section: Pharmacological Applications Of Phytochemicals In Pig Productionmentioning
confidence: 99%
“…YGF251, extracted from herbs including Phlomisumbrosa Turez , Cynancumwilfordii Hemsley , Zingiberofficinale Rosc , and Platycodi Radix , positively promotes growth performance, nutrient digestibility, immune function, and fecal gas emission in pigs. However, Dietary supplementation with 0.05% herbal extract YGF251 in low protein diets does not effectively improve growth performance ( 31 ). Studies show that supplementation of combined Chestnut (Ch) and Quebracho (Qu) increase the serum concentration of albumin and albumin/globulin ratio, but decreased creatinine, and did not influence growth performance ( 35 ).…”
Section: Pharmacological Applications Of Phytochemicals In Pig Productionmentioning
confidence: 99%